2000
DOI: 10.1046/j.1460-9568.2000.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival effects of BDNF and NT‐3 on axotomized rubrospinal neurons depend on the temporal pattern of neurotrophin administration

Abstract: This study shows that both BDNF and NT-3 can prevent cell death in axotomized adult rat rubrospinal neurons (RSNs), but that the efficacy of neuroprotection depends on the temporal pattern of treatment. At 8 weeks after cervical spinal cord injury, 51% of the RSNs had died. Subarachnoidal BDNF infusion into the cisterna magna for 4 weeks resulted in neuronal hypertrophy and 71% survival. Continuous infusion for 8 weeks into the lumbar subarachnoidal space with either BDNF or NT-3 gave similar survival rates, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 26 publications
4
79
1
Order By: Relevance
“…Our observation of neuronal size and number restoration is somewhat at odds with other authors who have reported the death of a significant proportion of rubrospinal neurons after axotomy. The response of rubrospinal neurons to axotomy is an issue that has been examined extensively, in rats predominantly (12,21), but also in mice (22) and opposums (23). Although neuronal atrophy seems to occur universally after axotomy, different rates of cell loss have been reported between and among species (12,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of neuronal size and number restoration is somewhat at odds with other authors who have reported the death of a significant proportion of rubrospinal neurons after axotomy. The response of rubrospinal neurons to axotomy is an issue that has been examined extensively, in rats predominantly (12,21), but also in mice (22) and opposums (23). Although neuronal atrophy seems to occur universally after axotomy, different rates of cell loss have been reported between and among species (12,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In the adult rat, some reports have suggested that SCI leads to the death of a sizable proportion of RS neurons (Houle and Ye, 1999;Mori et al, 1997;Novikova et al, 2000), while some other reports have brought evidence that the axotomized RS shrink but survive in an atrophic state (Kwon et al, 2002;Prendergast and Stelzner, 1976). These discrepancies of interpretation may result from methodological differences; in particular they may reflect the inherent difficulty to detect shrunken neurons.…”
Section: Cell Numbermentioning
confidence: 99%
“…In the rat, after a spinal cord lesion at cervical levels, axotomized reticulospinal (RS) neurons shrink and display modification in the expression of various molecules (Egan et al, 1977;Kwon et al, 2002Kwon et al, , 2004Novikova et al, 2000;Tetzlaff et al, 1991). In this species, the RNm regains a normal aspect if brain derived neurotrophic factor (BDNF) is provided (Kwon et al, 2002;Liu et al, 1999;Novikova et al, 2000). Because neurotrophic substances are uptaken at synapses, the amount of neurotrophic factors accessible to a neuron relates ultimately to the number of synapses that this neuron possesses.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Neurotropin-3 (NT-3) is one of the important neurotrophic factors. It can prevent atrophy of mature CNS neurons, and promote corticospinal tract axonal regeneration and recovery of hindlimb's function in spinal cord injured animal [10][11][12][13][14][15] and Hapner et al 16 had indicated that NT-3 could upregulate the TrkC expression of NSCs and promote for them to differentiate into neurons.…”
Section: Introductionmentioning
confidence: 99%